PERHITUNGAN PORTOFOLIO OPTIMAL DENGAN METODE MEAN-SEMIVARIANCE DAN MEAN ABSOLUTE DEVIATION - SUYASA, NI KADEK NITA SILVANA; DHARMAWAN, KOMANG; SARI, KARTIKA (E-Jurnal Matematika; Vol 10 No 2 (2021)DO - 10.24843/MTK.2021.v10.i02.p322, 2021)
Knowing and managing investment portfolio risk is the most important factor in growing and preserving capital. The purpose of this study is to determine the optimal portfolio using Mean-Semivariance and Mean Absolute Deviation methods. The Mean-Semivariance method is a method that uses semivariance -semicovariance as a measure of risk while the Mean Absolute Deviation method uses the absolute deviation between realized return and expected return as a measure of risk. This study uses stock index data of LQ45 period February 2017-July 2019. The results of this study are that the Mean Absolute Deviation method gives higher return and risk than the Mean-Semivariance method.